Association between plasma long-chain polyunsaturated n-3 fatty acids concentrations and cognitive function: findings from NHANES III - Li, Xiaojing; Huang, Zijie; Tian, Yueqin; Chen, Xing; Wu, Haidong; Wang, Tong (Frontiers in Psychology, 2024)
Background: With increased life expectancy, cognitive decline has emerged as a prevalent neurodegenerative disorder.Objective: This study aimed to examine the correlation between concentrations of Plasma long-chain n-3 polyunsaturated fatty acids (LCPUFAs) and cognitive performance in elderly Americans. Methods: Data were analyzed from older adults enrolled in two NHANES cycles. Participants completed four cognitive assessments, including the Immediate Recall Test (IRT), Delayed Recall Test (DRT), Animal Fluency Test (AFT), and Digit Symbol Substitution Test (DSST). Linear regression and restricted cubic spline modeling examined associations between plasma LCPUFAs levels and cognitive test outcomes. Results: The cohort included 610 adults aged 69 years on average, 300 (49.2%) males and 310 (50.8%) females. The median LCPUFAs concentration was 309.4umol/L, with an interquartile range of 244.7-418.9umol/L. In unadjusted and adjusted generalized linear regression model analyses, circulating LCPUFAs exhibited significant positive correlations with DRT performance. No relationships were detected among those with chronic conditions (chronic heart failure, stroke, diabetes). A significant association between LCPUFAs levels and DRT scores was evident in males but not females. Conclusion: Plasma LCPUFAs concentrations were significantly associated with DRT performance in males free of chronic illnesses, including heart failure, stroke, and diabetes. KEYWORDS plasma long-chain n-3 polyunsaturated fatty acids, cognitive function, delayed recall test, docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA)